The Intracellular Growth of M. tuberculosis Is More Associated with High Glucose Levels Than with Impaired Responses of Monocytes from T2D Patients - Martha Torres; María Teresa Herrera; Guadalupe Fabián-San-Miguel; Yolanda Gonzalez (Journal of Immunology Research)
Diabetes mellitus, a metabolic disease characterized by hyperglycemia and poor glucose control, is a risk factor for Mycobacterium tuberculosis (M. tuberculosis) infection and the development of active tuberculosis. To evaluate whether M. tuberculosis infection susceptibility is associated with an intrinsic factor in monocytes from type 2 diabetes (T2D) patients or it is associated with hyperglycemia per se, we analyzed TLR-2 and TLR-4 expression by flow cytometry and the cytokines IL-1β, IL-6, IL-8, IL-10, and TNF-α by cytometric bead array assays, either stimulated with TLR-2 and TLR-4 ligands or infected with M. tuberculosis in the whole blood from T2D patients (n=43) and healthy subjects (n=26) or in CD14+ monocytes from healthy subjects cultured in high glucose (HG) (30 mM). The intracellular growth of M. tuberculosis was evaluated by CFU counts at 0, 1, and 3 days in both monocytes from T2D patients and monocytes from healthy subjects cultured in HG. We did not find significant differences in TLR expression, cytokine production, or growth of M. tuberculosis in monocytes from T2D patients compared with those in monocytes from healthy subjects. Despite these results, in vitro assays of monocytes cultured with 30 mM glucose led to significantly increased TLR-2 and TLR-4 basal expression compared to those of monocytes cultured with 11 mM glucose (P<0.05). Conversely, the production of IL-6 by TLR-2 ligand stimulation, of IL-1β, IL-6, and IL-8 by TLR-4 ligand stimulation, and of IL-8 by M. tuberculosis infection significantly decreased in monocytes cultured in HG (P<0.05). Additionally, the intracellular survival of M. tuberculosis increased in monocytes in HG after day 3 of culture (P<0.05). In conclusion, HG decreased IL-8 production and the intracellular growth control of M. tuberculosis by monocytes, supporting the hypothesis that hyperglycemia plays an important role in the impaired immune responses to M. tuberculosis in patients with T2D.